STUDY OF PERSONALITY TRAITS AND THEIR RELATIONSHIP WITH LONG JUMP ACHIEVEMENT AMONG FOURTH-STAGE STUDENTS - Ismail Khalil, Dr. Raghad (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2024)
This research aims to explore the personality traits and long jump achievements of fourth-stage students and to identify the correlational relationship between personality traits and long jump achievements among these students.The descriptive method with a correlational approach was utilized. The study sample included fourth-stage students from the Faculty of Education for Girls, Department of Physical Education and Sports Science, University of Kufa, for the academic year 2023-2024, totaling (40) students.The personality traits scale with its (26) items representing (5) areas with three alternative answers (Yes, Somewhat, No) was applied, along with the long jump test. Results were analyzed using the SPSS statistical package.The research concluded the following:- Students possess a high degree of personality traits.- Students exhibit a high level of effectiveness in the long jump.- A positive correlation exists between personality traits and the effectiveness of the long jump among students.The researcher recommends:- The necessity of measuring students' personality traits, especially upon admission to the college, to establish their personal traits level.- Emphasizing the importance of focusing on students' psychological aspects as they impact their sports performance.- Conducting a comparative study between students of all four stages in terms of personality traits and the effectiveness of the long jump.